A coalition partnership of vision health through a health-promoting school program for primary school students in Taiwan. (September 2017) - Chang, Li-Chun; Guo, Jong-Long; Liao, Li-Ling; Peng, Hsiu-Ying; Hsieh, Pei-Lin
Myopia, the most common refractive error, is the most common cause of avoidable visual impairment among children and has reached epidemic proportions among children and young adults in urban areas of East and Southeast Asia that contain populations of Chinese ancestry. Moreover, vision health is an important theme of the health-promoting school program issued by the Ministry of Education in Taiwan. The aim of this study is to assess the impact of pre- and post-intervention proposed by the health-promoting school (HPS) model. The objectives are to understand whether the HPS model influenced the vision screening results and the attitude, knowledge level, and vision care behavior of the students involved. A prospective cohort study design was used to evaluate a vision health program. Four elementary schools, local education authorities, and one university in northern Taiwan established a coalition partnership to design a six-month program to combat myopia among students. The target population was 6668 school children from local elementary schools. For the purpose of this study, the outcome of visual acuity testing (in logMAR) was analyzed with a sampling of 373 school children (aged 11–12 years old) who were chosen from high prevalence of poor vision classes. After the HPS program, the attitudes, behaviors, and knowledge levels of the school children regarding vision health were significantly improved. The pre-intervention mean logMAR of all participating students ( N = 373) was –.10, which increased to –.19 after the intervention. Analysis using the Wilcoxon signed-rank test showed that the logMAR value was significantly improved after the intervention ( t = 2.13, p < 0.05). Our findings highlight the relevance and effectiveness of the coalition's efforts, which reinforces the usefulness of co-operatively implementing the HPS program.